Incorporating Entrepreneurial Practices into STEM Education: Development of Interdisciplinary E-STEM Model in High School in the United Arab Emirates - Eltanahy, Marwa (2020)
STEM education has been emphasized in the UAE education reform because science, technology, mathematics and engineering are considered as the main disciplines that reflect the development of a country’s economic situation. Although STEM education benefits all students, its professions do not stimulate them all. Students have the right to pursue any other career that satisfy their ambition. For more effective STEM implementation in its early stage in the UAE, there is a need for a practical E-STEM model to guide STEM educators to integrate entrepreneurial practices into their existing STEM courses to enhance students’ entrepreneurial act. An exploratory sequential design was conducted through mixed-method approach to collect qualitative data from 12 STEM leaders regarding how entrepreneurial practices could be incorporated into STEM education. Moreover, quantitative data was collected from 134 Science, Technology, Mathematics and Business teachers regarding the challenges that might eliminate this incorporation in the UAE. Results revealed that experiential learning through competency-based practices is the best ap proach to adopt interdisciplinary E-STEM model with high school students. However, some E STEM challenges were highlighted to be examined in the future research such as lack of STEM teachers’ knowledge about entrepreneurial learning. Further studies are recommended to in vestigate the impact of the developed interdisciplinary E-STEM model on enhancing students’ entrepreneurial competencies.